Eosin-mediated synthesis of polymer coatings combining photodynamic inactivation and antimicrobial properties. Issue 36 (5th September 2017) - Sautrot-Ba, P.; Contreras, A.; Abbad Andaloussi, S.; Coradin, T.; Hélary, C.; Razza, N.; Sangermano, M.; Mazeran, P.-E.; Malval, J.-P.; Versace, D.-L.
Abstract : Eosin-derived coatings exhibiting photodynamic bacterial inactivation and antibacterial properties. Abstract : Polymer coatings exhibiting photodynamic bacterial inactivation properties have been successfully engineered. Such coatings were obtained by photoinduced crosslinking of a PEG–diacrylate monomer associated with the eosin Y dye which was used as both a radical photoinitiator and an antibacterial agent. A dual curing process was followed by combining compatible and solvent-free polymerization mechanisms, i.e. Aza-Michael reaction and free-radical polymerization in the presence of amines. The kinetics evolution of the photopolymerization process was followed using in situ Fourier transform infrared spectroscopy, allowing for the elucidation of the underlying mechanistic pathways. The influence of eosin Y and amines on the thermal and mechanical properties of the films was evidenced and discussed in terms of crosslinking chemistry. The antibacterial properties of the coatings against two different strains ( Escherichia coli and Staphylococcus aureus) were evaluated on short and long terms, revealing that eosin confers both photodynamic inactivation and antimicrobial properties to the films. These coatings are therefore particularly promising for disposable medical devices.